2005
DOI: 10.1111/j.1475-6773.2005.00426.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Interorganizational Relationships among Outpatient Drug Treatment Organizations 1990–2000

Abstract: Both motivating and enabling factors promoted the formation of IORs by drug abuse treatment centers. Managed care also played a distinct role, in this case appearing to undermine interorganizational cooperation. Because IORs can improve access to care and quality, policy makers should consider using both incentives and support such as management training to promote IOR formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
5
0
1
Order By: Relevance
“…Program ownership type has been well documented to relate to treatment program practices and service offerings (D'Aunno, 2006;Wells, Lemak, & D'Aunno, 2005;Wheeler, Fadel, & D'Aunno, 1992). Program-reported state authorization agency data were included because analyses conducted by the study team indicated that treatment program practices vary according to the type of state agency (i.e., substance abuse, public health, and mental health) responsible for authorizing the program.…”
Section: Control Variablesmentioning
confidence: 99%
“…Program ownership type has been well documented to relate to treatment program practices and service offerings (D'Aunno, 2006;Wells, Lemak, & D'Aunno, 2005;Wheeler, Fadel, & D'Aunno, 1992). Program-reported state authorization agency data were included because analyses conducted by the study team indicated that treatment program practices vary according to the type of state agency (i.e., substance abuse, public health, and mental health) responsible for authorizing the program.…”
Section: Control Variablesmentioning
confidence: 99%
“…Specialized organizations are expected to be less likely to cooperate than are organizations with a broader activity scope (Wells et al 2005). The specialization dimension cuts across the dimensions above, although it is empirically related to the member benefit-public benefit distinction: the ''common good'' is a broader goal than the benefit of members, and public benefit organizations will therefore tend to be active in a broader array of fields than member benefit groups.…”
Section: Communitarian Organizationsmentioning
confidence: 98%
“…Third, considerations of efficiency lead organizations to establish ties to others in order to improve its input/output ratio, or at least appear to be trying to do so to funding third parties which see cooperation as beneficial to output (Wells et al 2005). Pooling of resources can improve efficiency on many counts.…”
Section: Determinants Of Interorganizational Tiesmentioning
confidence: 98%
“…Los estudios evidencian mayor cooperación en las áreas de servicio, debido a la percepción en la escasez de recursos -como mano de obra-y la necesidad de mantener una buena imagen de los servicios (Smith et al, 1995). En las áreas auxiliares, la cooperación es motivada también por la escasez de recursos, pero más de tipo financiero (Mark, 1985;Schermerhorn y Shirland, 1981;Wells, Lemark y d'Aunno, 2005).…”
Section: Contexto De La Investigaciónunclassified